Long‐standing overt ventriculomegaly without aqueductal stenosis: A case report. Issue 2 (12th December 2017) - Ikumi, Kazuhiro; Tsuboi, Takashi; Atsuta, Naoki; Takeuchi, Kazuhito; Koike, Haruki; Katsuno, Masahisa
Abstract: We report a case of long‐standing overt ventriculomegaly without aqueductal stenosis. A 66‐year‐old woman developed progressive gait disturbance. Her gait was wide‐based, with a difficulty in turning. Prominent macrocephaly was present, which suggests the presence of long‐standing hydrocephalus since childhood. Cognitive impairments were detected on neuropsychological tests. Cerebral magnetic resonance imaging revealed marked enlargement of the third and lateral ventricles. Aqueductal stenosis was not apparent; however, endoscopic third ventriculostomy partly ameliorated gait disturbance. Endoscopic third ventriculostomy can be a therapeutic option for long‐standing overt ventriculomegaly even if the aqueduct is patent.